Pengembangan Aplikasi Sistem Informasi Pelayanan Desa berbasis Website (SIMPEDE) pada Desa Dawuhan Kecamatan Poncokusumo Kabupaten Malang - Ahmad Shofi Nurur Rizal; Djoko Pramono; Arief Andy Soebroto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Dawuhan Village is located in the Poncokusumo District, Malang Regency, East Java. Dawuhan is a developing village with a population of 7115 people. However, in this case, administrative services and population data processing in Dawuhan village still use conventional methods, which still use book archives to process written data so that the processing of certificate documents and civil registration letters still encounters many problems. To solve this problem, an information system that handles letter requests is needed. This research was conducted to find out the Village Service Information System (SIMPEDE) is running effectively. Answering these problems, business process modeling, needs analysis, system design and implementation, and testing are carried out to find out the system is running as desired. Business process modeling generates AS-IS and To-Be business processes. Requirements analysis is done by identifying actor activities with the system, identifying functional and non-functional requirements, visualizing use case diagrams, use case scenarios, and sequence diagrams, then makes database design with MySql, as well as system interface design. System implementation produces a specification for hardware and software environment, the implementation of the source code, then produces a system interface according to what user expects.